Unplugged Coding with Traditional Snacks: A Quasi-Experimental Approach to Enchancing Early Childhood Computational Thinking - Amanda Yunissafara; Suharti Suharti; Mallevi Agustin Ningrum; Dhian Gowinda Luh Safitri (Jurnal Pendidikan Anak, 2026)
This study aims to describe the implementation of unplugged coding using traditional snack media to develop computational thinking skills in children aged 5-6 years. The lack of integration of local cultural elements in technology education is the primary background of this study. The research method used was a quantitative quasi-experimental design with a one-group pretest-posttest. Data were analyzed using a paired t-test to assess the significance of differences in children’s abilities before and after treatment. The results showed a significant improvement in decomposition, pattern recognition, and simple algorithmic skills after children interacted with traditional snack media. These findings prove that abstract computational concepts can be taught concretely and contextually through local wisdom. This research contributes to the development of early childhood education by providing an innovative model of digital learning without devices (unplugged) while preserving cultural values. Theoretically, these results strengthen the integration of ethnopedagogy into modern educational curricula and provide a foundation for digital literacy from an early age, without dependence on gadgets.